The Motivational Design of Digital learning Platforms using the (ARCS) Model and its Effectiveness in developing the Reading Comprehension among Middle School Students - Alobaidi, Adnan Hassen; Zeidan, Ashraf Ahmed (Journal of Educational and Psychological Sciences, 2023)
This Study aimed to Investigate the effect of the motivational design in digital learning Platforms on developing reading comprehension skills among middle school students. A quasi-experimental design was used, the research sample consisted of (50) students from the second intermediate grade students in Taif Governorate. They were divided into two equal experimental groups, with (25) students in each group. The first studied reading comprehension texts through digital learning environments based on motivational design (ARCS), and the second studied reading texts through a digital learning environment without using motivational design elements. The results showed that there were statistically significant differences at the level of significance (0.05 ≥α) between the mean scores of the two experimental groups in the post-measurement achievement test of reading comprehension, in favor of the first experimental group. the research recommended was using the motivational design in digital learning environments in teaching reading comprehension texts, teaching Arabic in general, and training teachers to design reading comprehension lessons after employing the elements of the ARCS motivational design model.